Pengaruh pemberian ekstrak Lidah Buaya (Aloe Vera) terhadap penurunan kadar glukosa darah pada Mencit (Mus Musculus) diabetes melitus - Hafizah, Nurul; Harleli, Harleli; Meliahsari, Renni; Irma, Irma (PT WIM Solusi Prima, 2025)
Type 2 diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia due to insulin resistance and pancreatic β-cell dysfunction. One non-pharmacological treatment approach considered safe, economical, and free from harmful side effects is the use of herbal plants, such as aloe vera (Aloe vera). This plant contains active compounds such as acemannan, flavonoids, and anthraquinones that have the potential to act as antihyperglycemic agents. This study aims to investigate the effect of Aloe vera extract administration on blood glucose levels in diabetic mice (Mus musculus). This study is an experimental laboratory study using a post-test only control group design. A total of 30 male mice were used, divided into five groups: positive control, negative control, and three treatment groups with aloe vera extract doses of 250 mg/kgBB, 300 mg/kgBB, and 350 mg/kgBB, respectively. Diabetes mellitus was induced using streptozotocin (STZ) at a dose of 150 mg/kgBB. Bivariate analysis was performed using a One-Way ANOVA test with a Post-Hoc LSD test. The results showed that aloe vera extract significantly reduced blood glucose levels (p<0.05), particularly at the 350 mg/kgBB dose. Therefore, it can be concluded that aloe vera extract has the potential to effectively reduce blood glucose levels in diabetic mice, especially at the highest dose tested. This study supports the potential of aloe vera as an antidiabetic phytopharmaceutical agent.